CSF1R mosaicism in a family with hereditary diffuse leukoencephalopathy with spheroids - Eichler, Florian S.; Li, Jiankang; Guo, Yiran; Caruso, Paul A.; Bjonnes, Andrew C.; Pan, Jessica; Booker, Jessica K.; Lane, Jacqueline M.; Tare, Archana; Vlasac, Irma; Hakonarson, Hakon; Gusella, James F.; et al. (Brain (London, England : 1878), 2016)
Mutations in the colony stimulating factor 1 receptor (CSF1R) have recently been discovered as causal for hereditary diffuse leukoencephalopathy with axonal spheroids. We identified a novel, heterozygous missense mutation in CSF1R [c.1990G > A p.(E664K)] by exome sequencing in five members of a family with hereditary diffuse leukoencephalopathy with axonal spheroids. Three affected siblings had characteristic white matter abnormalities and presented with progressive neurological decline. In the fourth affected sibling, early progression halted after allogeneic haematopoietic stem cell transplantation from a related donor. Blood spot DNA from this subject displayed chimerism in CSF1R acquired after haematopoietic stem cell transplantation. Interestingly, both parents were unaffected but the mother's blood and saliva were mosaic for the CSF1R mutation. Our findings suggest that expression of wild-type CSF1R in some cells, whether achieved by mosaicism or chimerism, may confer benefit in hereditary diffuse leukoencephalopathy with axonal spheroids and suggest that haematopoietic stem cell transplantation might have a therapeutic role for this disorder.